Contrasted mixing efficiency in energetic versus quiescent regions: Insights from microstructure measurements in the Western Mediterranean Sea. (July 2021) - Vladoiu, Anda; Bouruet-Aubertot, Pascale; Cuypers, Yannis; Ferron, Bruno; Schroeder, Katrin; Borghini, Mireno; Leizour, Stephane
Highlights: Two types of dynamical regions with contrasting turbulence properties are sampled. Mixing efficiency is estimated over a large range of turbulence intensities. Its variability is compared with previous observations, simulations and experiments. Abstract: Microstructure and CTD/LADCP measurements from the Western Mediterranean basin east of 5 ∘ E revealed two types of dynamical regions (Ferron et al., 2017), contrasted in terms of current magnitude, vertical shear, stratification and turbulent kinetic energy dissipation rate: energetic regions (Corsica Channel, Egadi Valley and Sicily Channel) and quiescent regions (Ligurian Sea, around Sardinia, and Tyrrhenian Sea). On average, the current speed and the buoyancy frequency in the energetic regions were twice as large as in the quiescent regions, and the vertical shear was five times as large. Turbulence properties inferred from the microstructure measurements were also contrasted, dissipation rates in the energetic regions being two orders of magnitude larger than in the quiescent regions. The present study investigates the variability of the dissipation flux coefficient, a measure of the mixing efficiency, in a rich assortment of dynamical regimes. This dataset covers the full range of turbulence intensities observed in previous studies based on field measurements, direct numerical simulations, and laboratory experiments alike. The dependency of the dissipation flux coefficient as a function of turbulence intensity for the quiescent and energetic regions frames the previously observed lower and upper bounds, respectively. A contrasting behaviour was revealed between the two types of regions. In the quiescent regions, the dissipation flux coefficient linearly decreases on average by one order of magnitude with turbulence intensity increasing by four orders of magnitude. On the other hand, in the energetic regions the dissipation flux coefficient exhibits a nearly constant value over 4 decades of turbulence intensity, before decreasing for very strong turbulence intensities. In contrast with other studies, this dataset shows no relationship between the Richardson number and the dissipation flux coefficient. This may be due to inadequate vertical sampling resolution of the currents, or to the high diversity of sampled turbulent regimes, contrary to previous studies focused on a single type of dynamical region or framework (such as the thermocline or shear instabilities).